2019
DOI: 10.1108/ecam-06-2018-0252
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the knowledge domains of value management: a bibliometric approach

Abstract: Purpose The purpose of this paper is to review the state-of-the-art of literature of value management (VM) and to map the VM domain to provide a launch pad for further knowledge development and dissemination. Design/methodology/approach This study employed CiteSpace bibliometric analysis software to systematically, comprehensively and accurately review the VM-related literature and to map the VM knowledge domain. Findings The results reveal the current VM knowledge base, clusters, research hotspot, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
(86 reference statements)
0
30
0
Order By: Relevance
“…This information is useful for identifying gaps in the current knowledge and suggesting the pathway for future research. In this study, the approach adopted is similar to the process suggested and utilised in previous studies (Zupic and Čater, 2015; Aria and Cuccurullo, 2017; Ekanayake et al , 2019). The standard workflow suggested in these studies (Zupic and Čater, 2015; Aria and Cuccurullo, 2017) is carried out in five stages: conceptualisation of research, collection of bibliometric data, analysis of collected data, visualisation and interpretation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is useful for identifying gaps in the current knowledge and suggesting the pathway for future research. In this study, the approach adopted is similar to the process suggested and utilised in previous studies (Zupic and Čater, 2015; Aria and Cuccurullo, 2017; Ekanayake et al , 2019). The standard workflow suggested in these studies (Zupic and Čater, 2015; Aria and Cuccurullo, 2017) is carried out in five stages: conceptualisation of research, collection of bibliometric data, analysis of collected data, visualisation and interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…In this section, the clusters of recycled concrete publications are analysed to identify outliers in the body of knowledge. Similar to the approach adopted by Ekanayake et al, (2019), cluster labels are selected from the noun phrases of each cluster, and the noun phrases are extracted from titles, keywords and the abstracts of the publications. Therefore, the top-ranked noun phrases have been selected as the cluster label.…”
Section: Conceptual Structure: Identification and Interpretation Of Cmentioning
confidence: 99%
“…Citation analysis has various types that can be defined such as direct citations (cited a new article by an older article), bibliographic coupling (relationship between articles) and co-citation coupling (relationship between documents cited) (Osareh, 1996). Bibliometric analysis as one of the most applicable statistical research methods has been used in numerous articles (Wu et al, 2020;Shang et al, 2020;Ekanayake et al, 2019). Bibliometric analysis is also used in this paper to analyze articles in the field of opportunity recognition.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Here, CiteSpace is a knowledge domain visualization software developed by Chen (2004). It is broadly utilized in different research areas such as computer science (Morar, Agachi 2010;Niazi, Hussain 2011;Yu et al 2019aYu et al , 2019d, medicine (Chen et al 2012), psychology (Zhang et al 2015), economy (Cui, Zhang 2018), and management (Ekanayake et al 2019).…”
Section: Data Collection and Analysismentioning
confidence: 99%